2008
DOI: 10.1007/s10495-008-0257-y
|View full text |Cite
|
Sign up to set email alerts
|

Critical effect of VEGF in the process of endothelial cell apoptosis induced by high glucose

Abstract: The underlying molecular mechanism whereby hyperglycemia causes endothelial cell apoptosis is not well understood. This study aims to elucidate the role of survival factor VEGF involved in the apoptosis of endothelial cells induced by elevated glucose. The present study confirmed that high concentration of glucose (25 mmol/l) significantly increased the apoptotic cell number in cultured primary human umbilical vein endothelial cells (HUVEC). Up-regulation of Bax/Bcl-2 ratio and activation of caspase-3 induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 50 publications
(72 reference statements)
7
57
1
2
Order By: Relevance
“…We demonstrated there was a different response to plant extract with cellobiose complex (cellobiose, sulphur, selenium and vitamin C) and to solution of cellobiose in immortalized MEF wt cells in contrast to primary MEF wt cells, where there was no significant effect, suggesting there were some differences in the receptors in the cells membrane, by which molecules could enter the cell, what was also previously explored by Pelengaris et al, [1]. In immortalized MEF wt cells we observed there was a dose response to plant extract in higher concentrations from 0.1 mg/mL to 1 mg/mL, but this was not in linear correlation with the selected dosage range in the plant extract, where much lower concentrations were needed for the same effect of apoptosis and cell death [4,5,15,22]. For example the concentration of the plant extract of 1 µg/mL induced 28.10% of apoptosis in immortalized MEF wt cells, while 1.000x higher concentration of the mentioned extract induced 18.77% of apoptosis due to the fact that in higher concentrations the cells underwent cell death or simply bursted in the process (Figure 6) [15].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…We demonstrated there was a different response to plant extract with cellobiose complex (cellobiose, sulphur, selenium and vitamin C) and to solution of cellobiose in immortalized MEF wt cells in contrast to primary MEF wt cells, where there was no significant effect, suggesting there were some differences in the receptors in the cells membrane, by which molecules could enter the cell, what was also previously explored by Pelengaris et al, [1]. In immortalized MEF wt cells we observed there was a dose response to plant extract in higher concentrations from 0.1 mg/mL to 1 mg/mL, but this was not in linear correlation with the selected dosage range in the plant extract, where much lower concentrations were needed for the same effect of apoptosis and cell death [4,5,15,22]. For example the concentration of the plant extract of 1 µg/mL induced 28.10% of apoptosis in immortalized MEF wt cells, while 1.000x higher concentration of the mentioned extract induced 18.77% of apoptosis due to the fact that in higher concentrations the cells underwent cell death or simply bursted in the process (Figure 6) [15].…”
Section: Discussionsupporting
confidence: 53%
“…In white 96-well-plate we transferred 40 µl of each samples and added 50 µl of 2X caspase buffer/1M DTT and 10 µl of DEVD substrate. We gathered 40 µg of protein from cells, untreated and treated with the plant extract in the presence or absence of inhibitor Z-VAD-FMK, to determine caspase activity and by measuring the proteolytic cleavage of the fluorogenic substrate Ac-DEVD-AFC (Bachem) has also shown in standard protocols [4]. Before absorbance measurement the plate was incubated at 37 0 C in the incubator with 5% CO 2 .…”
Section: Determination Of Cell Death Mts Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on apoptosis as it is a wellestablished effect triggered by hyperglycemia [21]. Accordingly, it has been previously shown that HG-induced apoptosis in HUVECs is accompanied by increased Bax/Bcl 2 ratio [21][22][23], that can be reverted, at least partly, by treatment with DDP-4 inhibitors [7]. Second, we did not investigate the possible effects of DDP-4 inhibitors on nitric oxide synthase (eNOS) expression and activity, as it was well beyond the scope of this study and in vitro and in vivo studies have already provided evidence linking GLP-1, DDP-4 inhibitors, eNOS and endothelial function [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that VEGF can prevent cell death in various conditions. For example, VEGF prevented apoptosis of human umbilical vein endothelial cells (HUVEC) from high glucose exposure [63]. In high glucose exposure, pretreatment of VEGF lowered ROS generation, calcium overload, Bax/Bcl-2 ratio, caspase-3 activation in HUVEC.…”
Section: Testis Enhanced Gene Transcript (Tegt)mentioning
confidence: 99%